1995
DOI: 10.1097/00005792-199509000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Whiplash Injury: A 2-Year Follow-Up Considering Features of Injury Mechanism and Somatic, Radiologic, and Psychosocial Findings

Abstract: With the increased incidence of whiplash injury following the introduction of compulsory car seat belts, a large number of reports have dealt with the aftermath of this condition. Previous studies, however, focused on somatic symptoms on the one hand or considered only psychological or neuropsychological variables on the other hand, often in loosely defined or selected groups of patients. No study so far has analyzed the long-term outcome in a nonselected group of patients using a clear injury definition consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
175
2
10

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(196 citation statements)
references
References 46 publications
9
175
2
10
Order By: Relevance
“…Our results were not in line with the prior studies' observations of pre-existing degenerative findings being related to a poor prognosis [5,31]. Signs of disc degeneration considered to be pre-existing were frequent but not related to more intense pain at neither baseline nor followup.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results were not in line with the prior studies' observations of pre-existing degenerative findings being related to a poor prognosis [5,31]. Signs of disc degeneration considered to be pre-existing were frequent but not related to more intense pain at neither baseline nor followup.…”
Section: Discussioncontrasting
confidence: 99%
“…In the acute stage the neck pain is attributed to soft-tissue injuries to the cervical region [18,24]. Neck pain and headache are the most frequently reported features of the condition [16], termed whiplash associated disorder (WAD) [20].…”
Section: Introductionmentioning
confidence: 99%
“…The QTF-cohort study [20] found chronic symptoms in 13%, 6 months after MVA. In an other study [19], 18% of WAD cases still had complaints after 2 years, while yet another study [18] reported a recovery rate at 66% after 18 months. Female gender was a risk factor for injury to the neck in two studies [9,16].…”
Section: Discussionmentioning
confidence: 88%
“…Studies on the recovery rate in WAD has shown variable results; 13-66% of recovery [13,[18][19][20]. The QTF-cohort study [20] found chronic symptoms in 13%, 6 months after MVA.…”
Section: Discussionmentioning
confidence: 99%